Medicaid Expansion and Racial and Ethnic Disparities in Access to Health Care: Applying the National Academy of Medicine Definition of Health Care Disparities - Hyunjung Lee PhD; Dominic Hodgkin PhD; Michael P. Johnson PhD; Frank W. Porell PhD (SAGE Publishing, 2021)
Since 2014, 32 states implemented Medicaid expansion by removing the categorical criteria for childless adults and by expanding income eligibility to 138% of the federal poverty level (FPL) for all non-elderly adults. Previous studies found that the Affordable Care Act (ACA) Medicaid expansion improved rates of being insured, unmet needs for care due to cost, number of physician visits, and health status among low-income adults. However, a few recent studies focused on the expansion's effect on racial/ethnic disparities and used the National Academy of Medicine (NAM) disparity approach with a limited set of access measures. This quasi-experimental study examined the effect of Medicaid expansion on racial/ethnic disparities in access to health care for U.S. citizens aged 19 to 64 with income below 138% of the federal poverty line. The difference-in-differences model compared changes over time in 2 measures of insurance coverage and 8 measures of access to health care, using National Health Interview Survey (NHIS) data from 2010 to 2016. Analyses used the NAM definition of disparities. Medicaid expansion was associated with significant decreases in uninsured rates and increases in Medicaid coverage among all racial/ethnic groups. There were differences across racial/ethnic groups regarding which specific access measures improved. For delayed care and unmet need for care, decreases in racial/ethnic disparities were observed. After the ACA Medicaid expansion, most access outcomes improved for disadvantaged groups, but also for others, with the result that disparities were not significantly reduced.